Giant placental chorangioma: Apropos of the first case treated by fetoscopy and laser photocoagulation in Peru - Novoa, Rommy H. (2018)
Placental chorioangioma is a non-trophoblastic benign tumor of rare presentation. It may be associated with complications of pregnancy when larger than 4 cm. We present the case of a pregnant adolescent with 25 weeks of gestation referred for prenatal management of a giant placental chorangioma that complicated pregnancy with hydramnios and severe fetal anemia. Fetoscopic laser ablation of the main nutrient vessel of the tumor was performed for the first time in Peru, which reversed complications and improved fetal prognosis.